Prognostic implications of autophagy and pyroptosis related genes in oral squamous cell carcinoma: research on bioinformatics and experiments - Qiao, Leshui; Si, Binghui; Xiao, Jiangtian; Song, Xiaoyu (Frontiers in Oncology, 2025)
ObjectiveOral squamous cell carcinoma (OSCC) is associated with poor prognosis, underscoring the urgent need to identify biomarkers that can predict patient outcomes and guide personalized treatment strategies. This study analyzes the prognostic potential of autophagy and pyroptosis-related genes in OSCC by bioinformatics approaches.MethodsClinical data and gene expression profiles for OSCC were obtained from the TCGA database, while autophagy and pyroptosis-related genes were retrieved from the GeneCards database. A prognostic model based on these genes was constructed using the LASSO Cox regression method. The performance of the model was evaluated through ROC curve analysis and survival analysis. Gene set enrichment analysis (GSEA) was performed to explore the functional pathways associated with these genes, and immune infiltration was assessed through immune profiling. The independent prognostic value of the genes included in the model was evaluated using multivariate Cox regression and nomogram analyses.ResultsEight autophagy and pyroptosis-related genes (BAK1, ATG5, VEGFA, GABARAPL1, RSL1D1, CYCS, TOMM20, and PGAM5) were found to have significantly lower overall survival (OS) in the high-expression group compared to the low-expression group in OSCC tissues. GSEA revealed that these genes were involved in pathways such as the Initial Triggering of Complement, the Role of Phospholipids in Phagocytosis, CD22-Mediated BCR Regulation, and the Role of Lat2/NATL/LAB in Calcium Mobilization. Furthermore, BAK1 and GABARAPL1 were positively correlated with immune cell infiltration in OSCC, while the other six genes showed negative correlations with immune infiltration. Notably, BAK1 and GABARAPL1 were identified as independent prognostic factors for OSCC, with BAK1 showing particularly strong diagnostic predictive potential. Functional assays revealed that silencing BAK1 in OSCC cell lines (SCC-15 and CAL-27) significantly inhibited cell proliferation and migration in vitro.ConclusionsOur findings suggest that the high expression of eight autophagy and pyroptosis-related genes in OSCC correlates with poor prognosis. In particular, BAK1 emerges as an independent prognostic marker with high diagnostic potential. These results offer promising insights into the development of gene-targeted therapies for OSCC, with BAK1 representing a potential therapeutic target.